2012
DOI: 10.1080/19361653.2012.716697
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Heterosexual College Students’ Attitudes Toward LGBT People

Abstract: This article may be used for research, teaching, and private study purposes. Any substantial or systematic reproduction, redistribution, reselling, loan, sub-licensing, systematic supply, or distribution in any form to anyone is expressly forbidden. The publisher does not give any warranty express or implied or make any representation that the contents will be complete or accurate or up to date. The accuracy of any instructions, formulae, and drug doses should be independently verified with primary sources. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
37
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(52 citation statements)
references
References 63 publications
13
37
0
2
Order By: Relevance
“…On the other hand, in this research, discriminatory attitudes towards women and homosexuals have been found to have lost their power as the degree of perceived liberalism increases. Political viewpoints have been dealt with in many researches related to attitudes toward different cultural groups (Christopher & Mull, 2006;Kirkpatrick, 1993;Laythe, Finkel & Kirkpatrick, 2001;Woodford et al, 2012) and in general, the level of liberalism appears to be related to positive attitudes towards women, homosexuals and individuals from different races/religions. Conservatism is characterized by features such as resistance to evaluating and considering new views and perspectives, loyalty to the social traditions, and exclusion and condemnation of members of the community who contradict them (Laythe et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in this research, discriminatory attitudes towards women and homosexuals have been found to have lost their power as the degree of perceived liberalism increases. Political viewpoints have been dealt with in many researches related to attitudes toward different cultural groups (Christopher & Mull, 2006;Kirkpatrick, 1993;Laythe, Finkel & Kirkpatrick, 2001;Woodford et al, 2012) and in general, the level of liberalism appears to be related to positive attitudes towards women, homosexuals and individuals from different races/religions. Conservatism is characterized by features such as resistance to evaluating and considering new views and perspectives, loyalty to the social traditions, and exclusion and condemnation of members of the community who contradict them (Laythe et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…This study obtained a variety of demographic data from a demographic questionnaire that gathered information relating to participants' gender identity, sexual orientation, race and ethnicity, age, level in school, religion, ability status, income level, and political ideology . The question about political ideology requests participants to rate themselves on a 7-point scale from strongly liberal to strongly conservative (Woodford et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Despite the prevalence of intergroup contact research, very little research has specifically examined the effect of intergroup contact with bisexuals on binegativity. Although most studies examining contact with LGB (lesbian, gay, and bisexual) individuals find that intergroup contact is associated with more positive attitudes toward LGB persons (Bowen & Bourgeois, 2001;Hinrichs & Rosenberg, 2002;Liang & Alimo, 2005;Steffens & Wagner, 2004;Stotzer, 2009;Woodford, Silverschanz, Swank, Scherrer, & Raiz, 2012), these studies often do not distinguish between contact with or attitudes toward lesbian/gay individuals and bisexuals (e.g., Hinrichs & Rosenberg, 2002;Woodford et al, 2012) or the quality and quantity of contact. Thus, the distinct qualities of binegativity compared to homonegativity and the lack of specificity in the prejudice reduction literature ultimately restrict our ability to draw clear conclusions regarding the impact of intergroup contact on attitudes toward bisexuals.…”
Section: Intergroup Contact With Sexual Minoritiesmentioning
confidence: 99%